Gliosarcomas. - Sousa, O (1998)
Gliosarcomas are rare tumors of the central nervous system with a poor prognosis. Histologically these tumors are characterized by an admixture of neoplastic glial cells and sarcomatous elements. Due to the scarcity of data in literature, the diagnosis is often missed and treatment is difficult. The authors report three cases of cerebral gliosarcomas and review the literature on this subject.